Pengaruh Model Cooperatif Learning Tipe Jigsaw terhadap Hasil Belajar Akidah Akhlak Siswa Kelas VII MTs Al-Khoiriyah Tapos Depok - Siti Nurasiyah; Muhammad Fahri; Ikhwan Hamdani (Jurnal Dirosah Islamiyah, 2022)
In an effort to improve the quality of education, it is also necessary to have an update in the field of education. One of the efforts to improve the quality of learning is by updating relevance or teaching and learning model approaches. It is said to be good and relevant if a teaching model during the learning process has succeeded in delivering it to achieve an educational goal. The purpose of this study was to determine the effect of cooperative learning or jigsaw type cooperative learning on the learning achievement of seventh grade students at MTs Al-Khoiriyah Tapos, Depok City. The method used in this study, entitled "The Influence of Cooperative Learning Models on Learning Outcomes of Moral Aqidah Students of Class VII MTs Al-Khoiriyah Tapos Depok" is a quantitative approach, the design that will be used in this study is pre-experimental (non-desings) where in This design is not yet a real experiment because there is an influence on the formation of the dependent variable originating from the participating external variables). From the results of hypothesis testing from the pretest and posttest, it shows that there are significant differences in learning outcomes of aqidah morals on reprehensible morals, riya and nifaq, which are significant between students who use the jigsaw type of cooperative learning model and students who use conventional learning. This can also be seen from the average results of students using the jigsaw type cooperative learning model, which is higher at 69.84 compared to students using conventional learning or before the implementation of learning with the jigsaw type cooperative learning model which is lower at 42.19. Based on the results that have been obtained, it can be seen that this jigsaw cooperative learning model has an effect on the learning outcomes of class VII students in the lessons of creed, morals, reprehensible morals, riya and nifaq. Keywords: Cooperative Learning Tipe Jigsaw, Learning Ooutcomes